Differentiating anxiety and depression: the State-Trait Anxiety-Depression Inventory. Issue 7 (3rd October 2018) - Renner, Karl-Heinz; Hock, Michael; Bergner-Köther, Ralf; Laux, Lothar
ABSTRACT: The differentiation of trait anxiety and depression in nonclinical and clinical populations is addressed. Following the tripartite model, it is assumed that anxiety and depression share a large portion of negative affectivity (NA), but differ with respect to bodily hyperarousal (specific to anxiety) and anhedonia (lack of positive affect; specific to depression). In contrast to the tripartite model, NA is subdivided into worry (characteristic for anxiety) and dysthymia (characteristic for depression), which leads to a four-variable model of anxiety and depression encompassing emotionality, worry, dysthymia, and anhedonia. Item-level confirmatory factor analyses and latent class cluster analysis based on a large nation-wide representative German sample ( N = 3150) substantiate the construct validity of the model. Further evidence concerning convergent and discriminant validity with respect to related constructs is obtained in two smaller nonclinical and clinical samples. Factors influencing the association between components of anxiety and depression are discussed.